Trigonometry

Someone please help!!!?

7. What is 1/cot(x) in terms of sine?

This is what I've got so far:
sin = 1/csc
tan = 1/cot

1+cot2(x) = csc2(x)
1/1+cot2(x) = 1/csc2(x)

  1. 👍 0
  2. 👎 0
  3. 👁 265
  1. 1/ctn=tan=sin/cos=sin/(1-sin^2)

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Express the function in the form f compose g. (Use non-identity functions for f and g.) u(t) = cot t/(9+cot t) {f(t), g(t)}=?

  2. Precalc?

    Suppose that Cot(theta) = c and 0

  3. Algebra, Trig

    You are standing at a base of a Ferris Wheel which is 4 m above ground while your friend is riding. The Ferris Wheel is 8m in diameter. Describe how the shape of the sine curve models the distance your friend is to the platform

  4. Trigonometry

    Verify the identity algebraically. TAN X + COT Y/TAN X COT Y= TAN Y + COT X

  1. Trig

    Write the following in terms of sin(θ) and cos(θ); then simplify if possible. csc(θ) - cot(θ)cos(θ) =

  2. Math

    Justin wants to evaluate 3cot(-5pi/4). Which of the following identities can he use to help him? Select two answers. cot(-theta) = cot(theta) cot(-theta) = -cot(theta) cot(-theta) = cot(-theta) cot(theta + pi) = cot(theta)

  3. MATHS - URGENT

    Write the expression in terms of sine only. 8(sin 2x − cos 2x)

  4. math

    Simplify and write the trigonometric expression in terms of sine and cosine: sin x +(cot x)(cos x) = 1/f(x) f(x)= ?

  1. Math

    Can you find (a) a sine graph which touches the lines y = 3 and y = 1? (b) a cosine graph which crosses the x-axis at x = 1 and x = −1? (c) a tangent graph which passes through the point (π/3, 0) and for which the line x= π/2

  2. Math

    Prove: Cot x cot 2x - cot 2x cot 3x - cot 3x cot x = 1

  3. Pre-Calculus

    Verify the identity. (csc(2x) - sin(2x))/cot(2x)=cos(2x) =csc(2x)/cot(2x) - sin(2x)/cot(2x) =csc(2x)/cot(2x) - cos(2x) Is this correct so far? If so then how would I continue? I got stuck on this part...

  4. cosine and sine HELP!

    Simplify and write the trigonometric expression in terms of sine and cosine: ((2+tan^2 x)(sec^2 x))-1 = (f(x))^2 f(x)= ???

You can view more similar questions or ask a new question.